Plasma Ascorbic Acid Levels in Critically Ill Pediatric Patients - Choi, Daniel Horim; Basu, Sonali; Levine, Mark; Steinhorn, David (Journal of Pediatric Intensive Care, 2022)
Ascorbic acid, or vitamin C, is a physiological antioxidant that has been found to be deficient in critically ill adults with sepsis and acute respiratory distress system. In adults, ascorbic acid supplementation has been shown to reduce the need for vasopressors and mechanical ventilation. This study aimed to describe the prevalence of ascorbic acid deficiency in critically ill pediatric patients. This prospective, single-centered study analyzed 34 patients aged 1 month to 18 years old with septic shock and/or acute respiratory failure requiring mechanical ventilation in a quaternary, urban, pediatric intensive care unit. Plasma ascorbic acid levels were measured by high-performance liquid chromatography within 24 hours of meeting eligibility criteria. The median level was 23.34 µM (IQR [11.45, 39.14]). Twenty-three patients had repeat samples that were collected 3 to 5 days later. The median for repeat samples was higher at 42.41 µM (IQR [13.08, 62.43]). Patients who were enterally fed had significantly higher levels than those who were not (62.4 ± 7.7 µM vs. 32.4 ± 7.1 µM; p = 0.03). Ascorbic acid levels vary widely among critically ill children with septic shock and/or respiratory failure requiring mechanical ventilation, but one-half of our patients had deficient levels that are typically seen in scurvy. Further studies are warranted to investigate the significance of low levels as well as the impact of normalizing levels through nutritional support.
Keywords: ascorbic acid; PICU; enteral nutrition